Use of lignocaine nebulization in post bronchoscopy patients: a study of 150 cases - Gul, Naveed; Manhas, Monica; Kalsotra, Parmod; Mir, Mehak Taban (International Journal of Research in Medical Sciences, 2020)
Background: To see the role of lignocaine nebulisation and to compare its role with use of steroids and bronchodilators alone in post bronchoscopy patients. Methods: In the present study, 150 patients, who underwent rigid bronchoscopy for removal of foreign body, were taken into consideration. Immediately after the rigid bronchoscopy, 100 patients were given nebulization and 50 patients were not nebulized. Out of 100 patients, 50 patients were given nebulization with steroids (budesonide) and bronchodilators (salbutamol) and 50 patients received nebulization with lignocaine 4%, steroids (budesonide) and bronchodilator (salbutamol). Results: In the present study, 38 patients (25.3%) were having complications like laryngobronchial spasm, laryngeal edema, cardiac arrest and respiratory arrest. Out of the 38 patients, 15 patients (39.5%) were having laryngobronchial spasm and 23 patients (60.5%) were having laryngeal edema. Out of 15 patients who had laryngobronchial spasm only 2 (13.3%) patients, who were nebulised developed this complication, while 86.7% cases of laryngobronchial spasm developed in non-nebulised patients. Out of 23 patients who developed laryngeal oedema, only 6 (26%) patients who were nebulised developed this complication, while 74% cases of laryngeal oedema developed in non-nebulised patients. Conclusions: In the present study it is concluded that both morbidity and mortality can be reduced by the use of nebulisation in the postoperative period after rigid bronchoscopy. Addition of lignocaine in nebulisation along with steroids and bronchodilators further reduces the morbidity and mortality in the postoperative period.